Matching Efficiency and Heterogeneous Workers in the UK - Elena Lisauskaite (Institute of Labor Economics (IZA), 2022)
The matching efficiency of the standard matching function is known to follow a pro-cyclical pattern. An observed rightward shift in the UK's Beveridge Curve after the Great Recession, suggests a decrease in the matching efficiency between vacancies and unemployed workers. This paper studies the changes in the labour market's efficiency over the period between 2001 and 2015 in the UK, and decomposes various factors behind it, such as industrial labour market segmentation and characteristics of unemployed, using the standard aggregate matching function. Consistent with the findings for the US (Barnichon and Figura (2015), Hall and Schulhofer-Wohl (2018)), I find that the UK labour market experienced a decrease in the matching efficiency during the Great Recession. However, contrary to what Barnichon & Figura (2015) observed in the US, composition of the labour market did not account for much of this decrease, leaving labour market tightness as the main factor for the decline in efficiency in matching unemployed workers and available vacancies. Accounting for labour market segmentation and worker heterogeneity, can explain 24% of movements in the matching efficiency over the period between 2001Q3 and 2014Q3.
Keywords: J6; J41; J42; 330; unemployment; mismatch; matching efficiency